(untitled) (Fiep Bulletin - online, 2014)
The professional formation in activities in contact with the nature, has a basic paper in the Chilean society, because is part as obligator content of the programs of Physical Education and is part of the public politics in health care and the promotion of the national tourism. The objectives of this study had been to verify if the professional formation of the students of the University Autónoma of Chile, Talca campus, is reaching the necessities and requirements for area in understanding the objectives, relating with the HMS and the professional action. The instrument of collection of data was a questionnaire with opened questions, one for each objective of the study. The sample was composed for 34 subjects in professional practical and that already they had attended a course in disciplines that had relative to the area. The results show that the future professionals understand the objectives of the activities, relate directly with the basic principles of the HMS and are capable to transform discipline knowledge in taught knowledge.